Predicting differential cross sections of electron scattering from tetrahydrofuran. (29th March 2017) - Zhang, Lulu; Sun, Weiguo; Zhang, Yi; Fan, Zhixiang; Hu, Shide; Fan, Qunchao
Abstract: A difference algebraic converging method for electron scattering from molecule ( DACMe ) is suggested based on the recently proposed difference converging method (DCM) to predict unknown differential cross sections (DCSs). The applications of the DACMe to electron scattering from tetrahydrofuran (THF) molecule at energies below 20 eV show that: (1) the DACMe DCSs excellently reproduce all the available experimental data; (2) the DACMe method correctly predicts unknown DCSs that may not be given experimentally; (3) the DACMe can be used as an economic and useful alternative method to predict the correct DCSs where such scattering data are required; (4) the DACMe method does not depend on the size and the stereochemistry structure of a scattering molecule; (5) the algebraic modification to the DCM enhances the computational efficiency of the DCM theoretical study by at least 110 times.